Folic acid and sperm quality improvement: insights from snRNA sequencing and RNA splicing mechanisms - He, Qifu; Zhang, Mingrong; Xiao, Sheng; Guo, Zijing (Frontiers in Nutrition, 2025)
Folic acid, an essential micronutrient in male reproductive physiology, serves as a critical cofactor in one-carbon metabolism by facilitating nucleotide biosynthesis and epigenetic methylation processes fundamental to spermatogenesis. Its metabolic role is characterized by two pivotal biochemical transformations: the remethylation of homocysteine to methionine and the subsequent generation of S-adenosylmethionine. These reactions collectively sustain nucleic acid synthesis, preserve genomic integrity, and modulate transcriptional regulation in developing germ cells. Compromised folate status disrupts small nuclear RNA (snRNA) maturation and methylation patterns, resulting in impaired spliceosome complex formation and compromised pre-messenger RNA (pre-mRNA) splicing accuracy. Such molecular perturbations generate defective transcripts that ultimately undermine proteomic homeostasis during spermiogenesis. Preclinical evidence demonstrates that folate deficiency induces chromosomal segregation errors, mitotic spindle checkpoint dysfunction, and concurrent oxidative/endoplasmic reticulum stress pathways—all converging to manifest as teratozoospermia, diminished motility, and elevated sperm DNA fragmentation indices. Folic acid supplementation can improve snRNA and spliceosomal function, leading to improve semen parameters, particularly in individuals with polymorphisms in folate-metabolizing enzymes such as MTHFR. However, treatment efficacy exhibits dose-dependence, temporal dynamics, pharmacogenetic variation, and synergistic interactions with concurrent micronutrient administration, underscoring the imperative for personalized nutritional approaches. Emerging single-nucleus RNA sequencing technologies have elucidated intricate regulatory circuitry connecting folate-responsive snRNAs with mRNA processing, miRNA-mediated silencing, and long noncoding RNAs (lncRNAs)-mediated chromatin remodeling. These findings propose candidate molecular signatures for monitoring therapeutic response. Notwithstanding these advances, the mechanistic interplay between folate metabolism and snRNA processing machinery remains incompletely characterized, and evidence-based clinical protocols for infertility management remain undefined. Future research directions should encompass: (1) multi-omics integration (epigenomic-transcriptomic-proteomic); (2) pharmacogenomic-guided intervention trials; and (3) dynamic splicing efficiency quantification platforms. Such approaches will enable precision therapeutic stratification to maximize clinical outcomes while mitigating potential adverse effects. This critical synthesis delineates the mechanistic nexus between folate-dependent snRNA regulation, RNA splicing fidelity, and spermatogenic competence, while advocating for biomarker-driven, genotype-tailored therapeutic paradigms in folate-responsive male infertility.